Evaluasi Tingkat Kematangan Sistem Informasi Manajemen Rumah Sakit Menggunakan ITIL (Information Technology Infrastructure Library) Versi 3 (Studi Pada : Rumah Sakit Umum Universitas Muhammadiyah Malang) - Mashuda Bahtiar; Suprapto Suprapto; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Generally Hospital of Muhammadiyah University of Malang is a private institution engaged in the field of health services. In conducting operations, General Hospital of University of Muhammadiyah Malang (RS UMM) utilize technology as supporting power. One of them by using Hospital Management Information System (SIMRS). This system is used by employees in helping to provide information related to inpatient, outpatient, pharmacy, logistics, and nutrition activities. The problem that arises is the lack of management control in conducting operations resulting in lack of validation of information that leads to errors and decreased business performance. such as data entry error, slow system access to certain hours, until loss of patient transaction data. To overcome this, the need for a controlling mechanism related to the management of information services is related to the value of the operations and services achieved by a company or organization in accordance with its intended purpose. From the results of research that has been done, the value of Maturity obtained in the domain Service Operation (SO) is 1.76 or is at level 2, and the Continent Service Improvement (CSI) domain is at Maturity 1.47 or level 1. Parties from home the pain itself, especially the field of IT wants the value of each 3 for the SO or for CSI. So to achieve the desired value, then given some recommendations that can help the IT in making decisions.